ANALYSIS OF CONSULTATION LENGTH IN KHYBER PAKHTUNKHWA, PAKISTAN - Idress, Muhammad; Syed Nasir Ali Shah; Iqbal, Waheed; Bazaz, Shafqat Ahmad; Bukhari, Faisal (Journal of Ayub Medical College Abbottabad, 2021)
Background: Consultation length is considered as direct measure of quality healthcare service and patient satisfaction. We analysed data collected from five different hospitals to inference the effects of sub-factors on consultation length. These factors have positive contribution in predicting the behaviour of consultation length. Methods: We performed cross-sectional study on first hand data collected from 386 participants using snow ball sampling method. The survey instrument was questionnaire and face to face interviews. We considered null hypothesis (H0=0) as means are equal against alternative hypothesis (H1 ‰ 0) for factors of time consumed by overall consultation, patient’s history, physical examination, and prescription writing. Data was also analysed by non-parametric univariate tests and multiple linear regression model. Results: Mean of consultation length is 22.466 minutes [CI: 21.420-23.512 and Î±=0.01]. Null hypothesis (H0=0) was rejected in favour of alternative hypothesis (H1‰ 0) by all factors due to sufficient evidence in data except prescription writing which failed to reject H0. Conclusion: We found factors had high spread in mean values and rejected null hypothesis indicating the duration of health workforces’ consultation is varying in different setups. Multiple factors contributed in formation of consultation length of doctors. Similar studies related to conservation of variation in consultation length must consider these factors. Eventually, such studies reporting this variation and its factors will add up in its efficacy and provisioning of appropriate consultation time totting up in patient’s satisfaction positively.